Tsunami-induced change in informal commerce at Laguna Phuket, Thailand. - Tan, Gloria Huixian. (2008)
This research project focuses on the informal commerce sector in Phuket, Thailand, with specific reference to Laguna Phuket, the Integrated Beach Resort at Bang Tao beach. After the tsunami in 2004, the area suffered severe damages but commercial recovery was quick. The research is conducted to identify changes in the informal commerce’s spatial patterns and suggest explanations for them. The research and analysis are done based on primary data collected from field studies at Laguna Phuket and unstructured interviews with the resort management personnel, informal vendors and tourists. Secondary data are obtained from past related studies and the internet. The modes of operation used to classify the informal commerce sectors include the roving businesses, fixed- location vendors and permanent shop fronts. The authors compared the informal commerce from an earlier, pre-tsunami research study conducted in 2004 with their recent findings. There were little overall changes except in the aspect of spatial pattern and the number of vendors. The reconstruction of stalls at certain areas resulted in the significant alteration of the layout. A significant increase in the number of Souvenir and Coffee Shop vendors was observed. Similar to the previous research, all businesses were still located along the beachfront.